Modulation of Postoperative Scarring with Tacrolimus and Octreotide in Experimental Glaucoma Filtration Surgery - Arslan, Sermal; Aydemir, Orhan; Guler, Mete; Dagli, Adile Ferda (Informa Healthcare, 2012)
Purpose: The purposes of this study were to investigate the effects of topically administrated Tacrolimus and Octreotide on modulation of postoperative scarring in experimental glaucoma filtration surgery and to compare the antifibrotic properties of these agents with mitomycin-C (MMC). Material and methods: A total of 28 New Zealand rabbits weighing 2.5-3 kg were randomly divided into a surgical control (SC) group and three experimental groups. Standard filtration surgeries were performed on the right eyes of all the rabbits. The rabbits in the SC group received only vehicle after the surgeries, whereas the rabbits in the three experimental groups were treated either with 0.4 mg/mL MMC during the surgery (MMC group) or with 0.3 mg/mL Tacrolimus drop four times a day (TT group) or with 10 mu g/mL Octreotide drop three times a day (OT group) for 14 days. The animals were killed on day 14, eyes were enucleated and histologically and immunohistochemically analyzed. Results: In SC group mean fibroblast, mononuclear cell number and fibroblast growth factor-beta (FGF-beta), transforming growth factor-beta (TGF-beta) immunostaining intensity was higher than all treatment groups. In OT group mean fibroblast number was lesser than MMC (p < 0.01) and TT (p < 0.05) group. In TT group mean fibroblast number was lesser than MMC group (p < 0.05). Mean mononuclear cell number was similar between MMC, OT and TT groups (p > 0.05). In MMC, OT and TT groups mean TGF-beta and FGF-beta immunostaining intensity was similar (p > 0.05). Conclusions: Topically administration of Tacrolimus and Octreotide effectively reduced the subconjuntival scarring response 2 weeks after experimental glaucoma filtration surgery.
Keywords: Glaucoma; Mitomycin-C; octreotide; Tacrolimus; Trabeculectomy